Association between Healthcare Provider Communication and Patient Adherence to Treatment Plans in Australia - Jones, Ava (Global Journal of Health Sciences, 2024)
Purpose: The aim of the study was to analyze the association between healthcare provider communication and patient adherence to treatment plans in Australia. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Effective healthcare provider communication in Australia significantly enhances patient adherence to treatment plans. Clear explanations and empathetic engagement from providers positively influence patient compliance. Conversely, poor communication or unclear instructions lead to lower adherence rates. These findings underscore the pivotal role of effective communication in fostering patient adherence and improving healthcare outcomes nationwide. Unique Contribution to Theory, Practice and Policy: Social cognitive theory (SCT), health belief model (HBM) & transactional model of stress and coping (TMSC) may be used to anchor future studies on association between healthcare provider communication and patient adherence to treatment plans in Australia. Implement targeted communication training programs for healthcare providers at all levels. These programs should emphasize skills such as active listening, patient-centered communication, and cultural competence. Advocate for policy initiatives that prioritize communication as a core component of quality healthcare delivery.